(untitled) (Chemical Engineering Research Bulletin, 2023)
Bioaccumulation of heavy metals in living organisms poses significant health risks, particularly through exposure to contaminated food and water. The human stomach is susceptible to bioaccumulation, which can lead to various adverse effects. This study aimed to investigate the efficacy of a common fruit, banana in eliminating lead (Ⅱ) and chromium (Ⅲ) heavy metals from aqueous and simulated stomach mediums so that further study could be performed to identify the chelation capability of that fruit. Synthetic aqueous solutions of lead and chromium were prepared, and a stomach-conditioned medium was simulated to mimic human stomach conditions. Bananas were introduced into the mediums, and removal rates were measured at specific residence times using AAS. The results revealed removal efficiencies of 25-86% for lead and 18-44% for chromium in the aqueous medium. There was slight change observed in the result of stomach medium, as the removal efficiencies became 49-86% for lead and 7-32% for chromium. The formation of new bonds was identified by FTIR analysis. These findings contribute to understanding the potential of bananas in reducing heavy metal accumulation in the human body, providing a basis for further research in this field. Chemical Engineering Research Bulletin 23(2023): 17-21